Transformational Leadership Versus Shared Leadership for Team Effectiveness - Thi Bich Hanh Tran; Anh Dung Vu (Asian Academy of Management Journal, 2021)
This study aims at investigating the effect of transformational leadership and shared leadership on dimensions of team effectiveness and the mediating role of teamwork orientation. The data were collected from members of working teams in companies of different fields in Vietnam. The results show that both transformational leadership and shared leadership are significantly associated to team effectiveness including team performance, quality of team experience, and team viability. The effects of transformational leadership are more robust compared to those of shared leadership while both leadership styles are dramatically relevant to team viability. In addition, teamwork orientation serves as a significant partial mediator in the relationship between transformational leadership, shared leadership, and dimensions of team effectiveness. The study is an early research in evaluating the effect of transformational leadership and shared leadership on three dimensions of team effectiveness, namely team performance, quality of team experience, and team viability. It is also the very first to explore the mediating role of teamwork orientation in the effect of leadership approaches on components of team effectiveness. The study offers interesting empirical evidence of an under-researched Asian emerging economy – Vietnam – so providing practical implications for companies in Vietnamese context in particular and similar Asian economies.